Social Rehabilitation Strategies for Homeless and Beggars: Evidence from Harapan Mulya Social Shelter, Jambi - Massuhartono; Edi Kurniawan; Marda, Syahrul; Rahmad Maulana (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Homelessness and begging remain persistent social problems that require comprehensive and context-specific interventions. This study analyzes the social rehabilitation strategies of Harapan Mulya Social Shelter in Jambi, Indonesia, which plays a central role in managing homeless individuals and beggars through institutional care. Using a qualitative case study approach, data were collected through semi-structured interviews with shelter staff and beneficiaries, participant observations of daily activities, and document analysis. Data were examined using Miles and Huberman’s interactive model to identify themes related to institutional strategies and their implementation. The findings reveal that the shelter adopts a structured four-stage rehabilitation pathway: outreach, resocialization, evaluation, and termination. Outreach establishes trust and provides immediate relief, while resocialization offers spiritual guidance, social counseling, and vocational training to foster independence. Evaluation functions as a feedback loop to monitor progress and adapt programs, and termination prepares beneficiaries for reintegration into society. These strategies demonstrate a holistic model of intervention that addresses both psychosocial and economic needs. However, the effectiveness of these efforts is shaped by supporting factors such as regulatory frameworks, government funding, and committed staff, as well as hindering factors including limited professional resources, inadequate infrastructure, and socio-economic inequalities that contribute to relapse. This study contributes to the literature by highlighting how social rehabilitation operates in a resource-constrained Southeast Asian context, extending global discussions on homelessness management. It also offers practical implications for policymakers and practitioners seeking to strengthen institutional care through integrated, culturally grounded, and cross-sectoral approaches.